Avaliação de procedimentos de digestão de amostras da cadeia produtiva de materiais escolares usando forno de micro-ondas com cavidade - Garcia, José Augusto (2014)
This study aimed to optimize the digestion of solid samples using microwave oven with closed flasks and understand the physicochemical parameters involved in this process. The development of this study was based on EN71 / 3 and CPSC-CH_E1001-08 standards. We performed a fractional factorial design (screening) to identify the significant variables for the process. The variables studied were volume of HNO3, heating program conditions, the addition of analytes and residual. The following responses were used to identify the most important variables: acidity of digested (%), the presence of the remaining solids digestion process (%), and recovery of previously added analytes (Pb and Cr). After identification of significant variables it was possible to set some parameters of the system and a new full factorial design 2³ (Design 1) was performed for 10 different types of samples, and the variables studied addition of H2O2, addition of analytes and sequential digestion. The responses observed were previously added recoveries of analytes (Ba, Cd, Cr, Hg, and Pb) and presence of the remaining solids digestion process (%). Data of Desing 1 was evaluated using multivariate analysis in order to detect clusters and trends among the strains. A new full factorial design 2³ (Design 2) was performed with selected samples and the following variables investigated: addition of H2O2, addition of analytes and volume of HNO3. The responses observed for Design 2 were recoveries of analytes previously added (Ba, Cd, Cr, Hg, and Pb), and comparison between the two systems digestion microwave assisted samples. The conclusions are that it is not possible to digest samples with different physicochemical characteristics in the same batch, the proposed system is not recommended for the determination of Cd and Hg and the proposed system can be used in order to perform a screening in samples.